IMPLEMENTASI RECYCLE LIMBAH KAYU HASIL PRODUKSI PLYWOOD DAN WORK WOOD MENJADI BAHAN BAKU PRODUK PARTICLE BOARD DI PT. KUTAI TIMBER INDONESIA PABRIK PROBOLINGGO - Setiawan, Agus; Putra, Arbie Suwanda; Agustianingsih, Fani Mulya; Ananda, Rahmah Rizki (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
This article examines the implementation of recycled wood waste produced into Particle Board products in PT Kutai Timber Indonesia (PT KTI) Probolinggo. With qualitative methods, the results of this study reveal that PT Kutai Timber Indonesia, as one of the industries engaged in manufacturing, one of which produced wood waste production that reached 29,390,790 kg in 2015, 27,716,130 kg in 2016, and 27,442,710 kg in the year 2017. The large amount of wood waste left over from this production encourages companies to recycle management by reusing it into raw material for particle board products. In implementing this recycle, PT KTI is able to utilize wood waste from plywood and work wood production into raw material for particle board products with a total efficiency value in 2015-2017 reaching Rp. 8,877,711,150.